Thermotopography of the rabbit eyeball cornea in case of impaired venous hemodynamics and laser therapy - Tanchyn , I.A.; Podolyk , M.V.; Savka, I.I. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. Thermometric and thermographic research methods play an important role in the diagnosis of ophthalmological diseases. Thermometry and thermography have become one of the screening diagnostic methods that allow determining the degree of activity of the pathological process, detecting relapses of the disease at different stages, predicting its course and assessing the effectiveness of conservative treatment. Aim. To study the possibility of using the thermometric method of research for early diagnosis and monitoring the effectiveness of laser therapy for venous stasis in the eyeball. Methods. The experiments were conducted on 45 rabbits of different sexes, aged 7–8 months, with a body weight of 2.5–3.0 kg, in which venous stasis was induced by diathermocoagulation of the vortex veins of the eye under thiopental anesthesia. Endovascular irradiation was performed daily using the universal laser irradiation device ALOU-2. Corneal temperature was measured with a point sensor of a medical semiconductor electrothermometer TEMP-61. Results. It has been established that temperature control allows for indirect, quantitative and dynamic assessment of morphofunctional changes vascular bed of the eye. The temperature of the cornea, measured with an electrothermometer at various points under the same measurement conditions, can serve as an indicator of changes in the intensity of blood circulation in the eyeball under conditions of venous stasis and laser therapy. Conclusion. Thermometric control is highly sensitive and sufficiently informative for assessing the effectiveness of laser therapy in conditions of venous congestion in the eyeball.